Perceptions and practices of dental faculty members of Khyber Pakhtunkhwa, Pakistan regarding smartphones as an adjunct teaching tool - Syed Muhammad Junaid; Brekhna Jamil; Usama Aurangzeb; Sana Shah; Natasha Nadeem (BMC Medical Education)
Abstract Background It is high time we acknowledged that the IT industry will determine our destiny given its rapid development. The demand to use smartphones and other forms of technology into healthcare is growing in tandem with the population. A great deal has been accomplished because of developments in computer science. This also needs to be a part of our educational practices. It would be incredibly beneficial to use cellphones to improve the learning possibilities for our medical students, since nearly all students and faculty members use them in some form. We need to gauge the faculty’s openness to new technologies and their thoughts on smartphones as a teaching tool before we can move forward with formal adoption. Methodology The faculty members of all the dental colleges in KPK were given a verified questionnaire. The survey was divided into two parts. The first one included data on population composition. The second survey enquired about the faculty’s present smartphone use to support their teaching. Results Our research found that teachers are already making use of smartphones in the classroom (Mean 2.65). Regardless, neither the college nor the university have formally launched using smartphones as a learning device. Conclusions Our investigation found moderate smartphone adoption among dental faculty in KPK (mean = 2.65/5.0), with significant variations across institutions and departments. While faculty members recognize potential benefits, current usage patterns suggest the need for structured implementation approaches and further infrastructure development.